The Relationship Between Family Support and the Level of Independence of the Elderly in Performing Daily Activities (BADL and IADL) in the Cakung Health Center Area, East Jakarta - Riasmini, Ni Made; Ramadhana, Dhea; Hartini, Tien (Caring : Jurnal Keperawatan, 2025)
The increasing number of elderly populations has an impact on the problems experienced by the elderly. Chronic disease is a health problem in the elderly that can affect their independence in carrying out daily life activities. Limitations in carrying out activities require family assistance, because the family is the main support system for the elderly. Family support will increase the spirit, self-esteem, and ability of the elderly in living their lives. The purpose of the study was to determine the relationship between family support and the level of independence of the elderly in carrying out daily activities in the Cakung Health Center work area, East Jakarta. This study is a quantitative study with a Cross Sectional design and using the Purposive Sampling technique. The sample size used was 62 elderly people with chronic diseases with data analysis using the Chi-Square Test. The results of the study showed that there was a relationship between family support and the level of independence of the elderly in carrying out basic daily activities (BADL) and instrumental (IADL) with a p value = 0.000 (p <0.05). Family empowerment is very important in facilitating the elderly who experience limitations, so that the elderly can still be active according to their abilities.